WATER POLLUTION IN YOGYAKARTA 1926–1942 - Setiawati, Nur Aini; Supratno, Edy; Utami, Santi Muji; Primaditya, Krisnanda Theo (UI Scholars Hub, 2025)
Water pollution in Yogyakarta has a long history dating back to the colonial era in 1926. Therefore, the main issue addressed in this writing is why water pollution occurred in Yogyakarta from 1926 to 1942. Basically, there are two factors influencing water pollution, namely natural factors and human factors. Using a historical research method, this study aims to examine water pollution in the Yogyakarta region, so that the government and the community can seek solutions. The sources used include collections from Algemeen Handelsblad voor Nederlandsch-Indie, De Locomotief, De Nieuwe Vorstenlanden, De Preanger Bode, and contemporary newspapers. The research findings on water pollution in Yogyakarta from 1926 to 1942 reveal that water pollution in the Yogyakarta region began when the population density increased. The arrival of the Dutch and Eastern foreigners increased the population, and their basic needs led to the pollution of clean water. Human needs caused the exploitation of natural resources, particularly water and human resources in Yogyakarta.